Pengaruh Aksesibilitas Jalan Ende – Nuabosi Terhadap Peningkatan Perekonomian Masyarakat Kecamatan Ende - Baje, Djuan Charlos Bedi; Sidyn, Thomas Aquino Arif; Radja, Veronika Miana (TEKNOSIAR, 2024)
Nuabosi is one of the villages in the Ende District area, where this village helps improve the economy of Ende District in terms of meeting economic needs, namely in the form of various agricultural and plantation products. However, even though Nuabosi Village is sufficient to meet the economic needs of Ende District, distance and inadequate infrastructure conditions are some of the factors that influence the level of accessibility in Ende District. This research aims to determine the value and level of accessibility in the villages of Ende District. The accessibility measuring parameter data used is travel time, road pavement conditions, supporting facilities, and travel rates or costs. Data analysis uses quantitative descriptive analysis and crosstab analysis methods, using the total accessibility calculation formula. The results of the analysis based on a review of accessibility parameters and crosstabs show that the highest accessibility value for each village is Ria Raja Village with a value of 2.18 and the lowest is Tina Bani Village with a value of 0.37. The average level of accessibility in Ende District as a whole is 0.83, indicating a high level of accessibility, where the existing road conditions can influence the improvement of the economy of the people in Ende District. Crosstab analysis also shows that most of the factors determining accessibility are related to the socio-economic conditions of the community.